Cuidados paliativos según dimensiones de calidad de vida en Adultos Diabéticos e Hipertensos - Inca Ninabanda, Magaly Elizabeth (2019)
Globally, chronic noncommunicable diseases hurt health systems due to the high morbidity and mortality rate. Diabetes mellitus and arterial hypertension are among the leading causes of death. Palliative care applied in these cases improves the life quality of the patient and this family from the diagnosis of the disease until his last days of life. To establish the link between the dimensions of life quality of patients who are affected in diabetic and hypertensive adults treated in the Health Centers of Chambo-Riobamba District according to the palliative actions described in the Clinical Practical Guide of the Ministry of Public Health of Ecuador and the nurse taxonomy. A descriptive, documentary study was carried out, and the study population was made up of 101 people with diabetes and 188 hypertensive patients. In the sociodemographic characteristics, the age of the age group of more than 65 years predominated, female gender, mixed ethnic self-identification and level of primary education. The central dimension affected was the adaptation to the limitations. Through the bibliography consulted, no evidence links the palliative care of the clinical practice guide and the nurse taxonomy. However, nursing actions based on taxonomy show similarity in the care of the diabetic and hypertensive individual.